Economic estimation of the mineral resource base of Donbass: status and prospects - S. M. Popov; E. A. Popova; I. G. Tumoian (Известия высших учебных заведений: Геология и разведка, 2023)
Background. The main deposits of Donbass and their mineral resource potential are considered.Aim. To develop a strategy for the socio-economic development of Donbass under contemporary political and economic conditions, with a focus on the development of human capital and further integration with the Russian Federation, CIS, and friendly countries.Materials and methods. A multipronged approach was used to define the contours, directions, and stages of the socio-economic development of Donbass.Results. The conducted analysis of the current state of the mineral resource base of Donbass revealed the most significant types of mineral resources for Donbass economy. An economic estimate of the cost of mineral resources extracted in Donbass and their market demand was obtained. Various types of resources were ranked in terms of their significance for Donbass economy.Conclusion. An approach to an integrated assessment of the expenses associated with the restoration of the mineral resource base of Donbass is proposed. In this respect, priority directions of economic activities are established.